2008
DOI: 10.1123/rsj.32.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Users and Nonusers of a Campus Recreation Center

Abstract: College students' physical activity provides protection against weight gain and chronic disease. Convenient exercise facilities have been correlated with physical activity. This study examined use of a college recreational facility among a sample of undergraduates, personal and demographic factors related to facility use, and factors predictive of facility use. A sample of 1,700 undergraduates was randomly selected and mailed a survey about health behaviors and recreation-center use. Facility users were more l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 8 publications
(6 reference statements)
2
22
0
Order By: Relevance
“…In response to this issue, colleges and universities have been prompted to take considerable interest in their fitness and recreational facilities and programs (Miller, et al, 2008). The U.S. Department of Labor and the Bureau of Labor Statistics (2009) reported that numerous college students engage in frequent sedentary behavior including spending hours in classrooms, time on school work and studying, using computers, and using video gaming systems.…”
Section: Obesity and Lack Of Physical Activitymentioning
confidence: 99%
See 4 more Smart Citations
“…In response to this issue, colleges and universities have been prompted to take considerable interest in their fitness and recreational facilities and programs (Miller, et al, 2008). The U.S. Department of Labor and the Bureau of Labor Statistics (2009) reported that numerous college students engage in frequent sedentary behavior including spending hours in classrooms, time on school work and studying, using computers, and using video gaming systems.…”
Section: Obesity and Lack Of Physical Activitymentioning
confidence: 99%
“…Results of a study by Miller et al (2008), assessing characteristics of users and nonusers revealed that males were more likely to use the recreational facilities as opposed to females. Students participating were more likely to be lower-standing students (freshman and sophomores), and more likely to live on campus.…”
Section: Usage Patternsmentioning
confidence: 99%
See 3 more Smart Citations